Step-by-step explanation:
(1/12)^-2b x 12^-2b+2=12
12^-(-2b) x 12^-2b+2=12
12^2b+(-2b+12)=12
2b-2b+12=12
=1
Answer:
7 divided by 2
Step-by-step explanation:
Answer:
i believe it is the first answer.
Step-by-step explanation:
So, first lets define our variables:
let x = the number of dimes
let y = the number of nickels
so our first equation would be x+y = 16
Since dimes are 10 cents and nickels are 5 cents the next equation would be as follows:
.10x+.05y = 1.35
now change the first equation so y = -x+16
now substitute:
.10x+.05(-x+16) = 1.35
then multiply so you get .10x+-.05x+0.8=1.35
combine like terms and you get .05x+0.8 = 1.35
then subtract 0.8 from both sides and you get .05x = 0.55 then subtract
and you get x = 11 then substitute 11 for where x should be and you should get y = 5
So, you have 11 dimes and 5 nickels